Hierarchical composite-solid-electrolyte with high electrochemical stability and interfacial regulation for boosting ultra-stable lithium batteries - Sun, J. (2021)
Solid-state electrolytes have drawn enormous attention to reviving lithium batteries but have also been barricaded in lower ionic conductivity at room temperature, awkward interfacial contact, and severe polarization. Herein, a sort of hierarchical composite solid electrolyte combined with a “polymer-in-separator” matrix and “garnet-at-interface” layer is prepared via a facile process. The commercial polyvinylidene fluoride-based separator is applied as a host for the polymer-based ionic conductor, which concurrently inhibits over-polarization of polymer matrix and elevates high-voltage compatibility versus cathode. Attached on the side, the compact garnet (Li6.4La3Zr1.4Ta0.6O12) layer is glued to physically inhibit the overgrowth of lithium dendrite and regulate the interfacial electrochemistry. At 25 °C, the electrolyte exhibits a high ionic conductivity of 2.73 × 10−4 S cm−1 and a decent electrochemical window of 4.77 V. Benefiting from this elaborate electrolyte, the symmetrical Li||Li battery achieves steady lithium plating/stripping more than 4800 h at 0.5 mA cm−2 without dendrites and short-circuit. The solid-state batteries deliver preferable capacity output with outstanding cycling stability (95.2% capacity retained after 500 cycles, 79.0% after 1000 cycles at 1 C) at ambient temperature. This hierarchical structure design of electrolyte may reveal great potentials for future development in fields of solid-state metal batteries.